отнимаем от модуля большего числа меньшее число по модулю
и ставим знак плюс (или пропускаем его)
- 3 - (-5)
|-3| = 3
|-5| = 5
5 - 3 = +2 = 2
- 1 1/2 - (-3 1/2)
|-1 1/2| = 1 1/2
| -3 1/2| = 3 1/2
3 1/2 - 1 1/2 = + 2 = 2
или
- 3 - (-5) = -3 + 5 = + 2 = 2
отнимаем от модуля большего числа меньшее число по модулю
и ставим знак плюс (или пропускаем его)
- 3 - (-5)
|-3| = 3
|-5| = 5
5 - 3 = +2 = 2
- 1 1/2 - (-3 1/2)
|-1 1/2| = 1 1/2
| -3 1/2| = 3 1/2
3 1/2 - 1 1/2 = + 2 = 2
или
- 3 - (-5) = -3 + 5 = + 2 = 2